DAMPAK MEDIA MASSA TERHADAP PENDIDIKAN ISLAM - Mira Rahmayanti Sormin (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
AbstractScience and technology that will continue to develop should not make pessimists even surrender, humans should not follow science and technology then simply become slaves to technology but science and technology that must be in the hands of humans or under human control. This hope can be realized if between science and technology and morals go together. Islam as a universal religion and only religion that is able to protect individuals, families, communities, amidst this rapidly changing world situation. Through Islamic religious education, will it be able to deal with the phenomenon caused by the advancement of current information that is displayed through mass media and social media.